Strategies for refining the Jeonse deposit return guarantee system - Yoon Sang Moon (Korea Development Institute (KDI), 2023)
Jeonse, a housing lease model unique to Korea, has long served as a cornerstone of housing security for many families. However, recent significant fluctuations in housing prices have highlighted concerns such as underwater jeonse and reverse jeonse, amplifying calls for reform. A crucial step in addressing these challenges and ensuring the stability of the jeonse system is to expand the scope of the Guarantee for a Return of Jeonse Deposit. In pursuit of this, it is important to accurately reflect risks in return guarantees and to consolidate jeonse guarantees under the unified framework of the Guarantee for a Return of Jeonse Deposit.
Keywords: 330